Determination of Morphine in Pharmaceutical Products by On-Line Solid-Phase Extraction and High-Performance Liquid Chromatography. (12th June 2016) - Yang, Yan-Ling; Ye, Xiao-Xue; Li, Yu-Sang; Tan, Zhi-Fang; Jiang, Ji-Zhou
ABSTRACT: A method for the rapid determination of morphine in Chinese medicines was developed using on-line solid-phase extraction combined with double-ternary gradient liquid chromatography. Licorice tablets and camphor tincture were used as representative examples of traditional Chinese medicine. The results indicated that morphine provided a linear response from 0.0239 to 0.239 m g mL −1 . The average recovery was as high as 99% with a relative standard deviation of 0.9%. Moreover, compared with conventional off-line solid-phase extraction and liquid chromatography, this approach offered a significant reduction in the analysis time. This method may provide for more efficient determination of morphine in traditional Chinese medicine.